Addictive phone use and academic performance in adolescents. Issue 1 (10th September 2019) - Domoff, Sarah E.; Foley, Ryan P.; Ferkel, Rick
Abstract: Adolescents are among the highest utilizers of Smartphones and social media applications (apps) in the United States. There has been increased concern that youth may become dependent on ("addicted to") Smartphones, yet limited research has considered excessive use (beyond that of hours of phone use) in adolescents. To address this gap, we measured addictive phone use and its association with academic performance in a sample of 641 adolescents. We found that our measure of addictive phone use (Addictive Patterns of Use scale [APU]) had strong psychometric properties and associated with hours of social media use and media multitasking. Additionally, APU associated with poorer academic performance, over and above hours of school day social media use and social media multitasking during homework. Thus, dependence on Smartphones may be a distinct risk factor for poor academic performance. Longitudinal research should be utilized to confirm our findings and provide evidence for directionality.